PERKECAMBAHAN DAN PERTUMBUHAN SEMAI Artocarpus altissimus J.J. Smith - Sahromi, Sahromi (Buletin Kebun Raya, 2013)
The research was conducted to understand seed germination and seedling growth of Artocarpus altissimus. The experimental design used was completely randomized with 2 factors, i.e. seed storability and media factors for the response capacity of germination, media and NPK fertilizer factors for seedling growth response (height and number of leaves). The result showed that A. altissimus seeds had long enough storability/ potential age without a period of dormancy. Storability, media and interaction both showed very significant effect on the germination capacity with the highest mean value on the storability category of 3 and 1 month and media category of compost and sand. On variable of seedlings height, NPK fertilizer showed significant effect, media and interaction of media and NPK had very significant effect with the best factor category was a media category of TSKn (soil, chaff and manure).